Why Are Micromerchants Still Reluctant To Use Digital Payments? Case Study: South Jakarta Msmes - Munir Azhari; Wiwit Damayanti; Feriandy Feriandy; Haspul Naser (UNIVED Press, 2025)
The adoption of digital payments by micromerchants in South Jakarta remains low. This study aims to investigate the reasons behind this reluctance, identify the factors that contribute to it, and suggest potential solutions. Qualitative research method was used. The research sample consisted of microentrepreneurs in the culinary, food and beverage, grocery, and home laundry sectors. Data were collected through interviews and observations in order to gain a more detailed understanding. The findings indicate that a significant proportion of small entrepreneurs remain reluctant to utilize digital payments because of a lack of comprehension regarding its utilization. This underscores the necessity for the provision of education and training to micro-merchants regarding the advantages and operational aspects of digital payments. This could potentially enhance the adoption of digital payments among micromerchants and facilitate more efficient business operations.